CAMPUR KODE DIALOG ANTAR TOKOH DALAM NOVEL JARAK ANTARBINTANG KARYA NAIMMAH NUR AINI - Sintiya Permata Indah; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe background of this research is to find out the code-mixing of dialoguesbetween characters in the novel Antarbintang Distance. The theory used in thisresearch is the form of code mixing, the type of code mixing and the function ofcode mixing. The method used is descriptive method. The form of research isqualitative research. The data collection technique is a documentary studytechnique. The results of data analysis contained 130 forms of code mixing,which were divided into 62 forms of words, 33 forms of phrases, 11 forms ofbaster, 8 forms of idioms and 16 forms of clauses. There are 118 types of codemixing, which are divided into 112 types outward and 6 types inward. There are117 code mixing functions which are divided into 43 affirming or convincingfunctions, 12 familiarizing functions, 1 respecting function, 9 prestige enhancingfunctions, 47 topic adjustment functions and 5 feeling functions. This researchhas a relationship with Indonesian Language Subjects in SMP class IXCurriculum 2013 which is recommended as a reference for exemplum textmaterials.Keywords: Sociolinguistics, Code Mixing, Novel